A low-protein, high carbohydrate diet induces increase in serum adiponectin and preserves glucose homeostasis in rats - Ceolin, Patricia; De Franca, Suelem A.; Froelich, Mendalli; Dos Santos, Maisa P.; Pereira, Mayara P.; Queiroz, Thais S.; Da Silva, Flavia H. S.; Lisboa, Patricia C.; Andrade, Claudia M. B.; Baviera, Amanda M. [UNESP]; Kawashita, Nair H. (Acad Brasileira De Ciencias, 2019)
The aim of this study was investigate the effects of a low-protein, high-carbohydrate (LPHC) diet introduced to rats soon after weaning. The animals were distributed in the following groups: LPHC45: fed an LPHC diet (6%-protein. 74%-carbohydrate) for 45 days: C-45: fed a control (C) diet (17%-protein, 63%-carbohydrate) for 45 days; R (Reverse): fed with LPHC for 15 days followed by C diet for 30 days. The LPHC45 group showed alterations in the energetic balance with an increase in brown adipose tissue, and in glucose tolerance, and lower final body weight, muscle mass and total protein in blood when compared with C-45 group. The HOMA-IR index was similar between LPHC(45 )and C-45 groups, but this parameter was lower in LPHC45 compared with R groups. Serum adiponectin was higher in LPHC45 group than C-45 and R groups. The R group presented higher fed insulin than C-45 and LPHC45 and higher T4 compared with C-45 group. Total cholesterol in R group was higher when compared with LPHC45 group. Thus, the data show that the change of the diet LPHC for a balanced diet led to different metabolic evolution and suggest that the different response can be due to different levels of adiponectin.
Keywords: low-protein; high-carbohydrate diet; post-weaning period; HOMA-IR; adiponectin